(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article "Methodological analysis of monitoring and evaluation". Traditional means of control, information about the subject of research are given.